Assessment of Administrative Practices on Management of Eco-Friendly Initiatives in Public Secondary Schools in Kirinyaga County, Kenya - Karanja Sellah Mugure; Lucy Muthoni Murage; Mugo David Gitumu (Journal of Research and Academic Writing, 2026)
The advocacy for sustainable practices in educational institutions globally has grown imperative due to issues such as climate change, deforestation, and waste-management. Public high schools play a crucial role in educating learners and staff about ecological stewardship, thereby contributing to sustainable development. However, management of eco-friendly initiatives in secondary schools is wanting. The study examined the status of administrative practices on sustainability management of eco-friendly initiatives in public secondary schools in Kirinyaga County, Kenya. Study objectives included; the level of teachers’ awareness and extent of curriculum integration. Guided by the Institutional Theory, the study adopted a descriptive survey research design. Target population consisted of 172 principals and 1160 teachers. Stratified random sampling was employed and using 10% of target population, a sample size of 17 principals and 116 teachers were selected. Questionnaire was used to collect data from teachers while interview schedule was used for principals. Data was analysed through descriptive statistics and thematic analysis. Results revealed a moderate level of teacher awareness where 40.0% were neutral, 32.7% agreed and 27.3% disagreed. On the extent of curriculum integration, 38.84% of principals were neutral, 35.13% agreed and 26.03% disagreed. The study concludes that administrative practices have been ineffective in operationalising, communicating, and sensitising the teaching staff on green initiatives. The study recommends that school heads through departments, develop and operationalise practical cross-curricular integration matrices that explicitly guide teachers on fusing green concepts into daily lesson schemes. The study would be significant to educational and environmental policy makers for it provides useful knowledge on management of eco-friendly initiatives.